Louse-Borne Relapsing Fever with Meningeal Involvement in an Immigrant from Somalia to Italy, October 2015 - Zammarchi, Lorenzo; Antonelli, Alberto; Bartolini, Laura; Pecile, Patrizia; Trotta, Michele; Rogasi, Pier Giorgio; Santini, Maria Grazia; Dilaghi, Beatrice; Grifoni, Stefano; Rossolini, Gian Maria; Bartoloni, Alessandro (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2016)
Borrelia recurrentis, transmitted by Pediculus humanus humanus, is the etiological agent of louse-borne relapsing fever (LBRF). Currently the main focus of endemicity of LBRF is localized in East African countries. From July 2015 to October 2015, 36 cases of LBRF have been diagnosed in Europe in immigrants from the Horn of Africa. Here we report a case of LBRF with meningitis diagnosed in Florence, Italy, in an immigrant arrived from Somalia. In October 2015, a 19-year-old Somali male presented to the emergency department of the Azienda Ospedaliero Universitaria Careggi, Florence, Italy, with a 3-day history of high fever. The patient had disembarked in Sicily 10 days before admission after a long migration trip from his country of origin. On clinical examination, neck stiffness was found. Main laboratory findings were thrombocytopenia, increased procalcitonin, and increased polymorphonucleates in the cerebrospinal fluid. Suspecting a possible meningitis, the patient was treated with ceftriaxone, pending results of laboratory testing for malaria, and developed severe hypotension that was treated with fluid resuscitation and hydrocortisone. Hemoscopic testing revealed the presence of spirochetes and no malaria parasites. The patient rapidly improved with doxycycline for 7 days and ceftriaxone for 11 days, then was lost to follow-up. Total DNA from blood was extracted, and amplification and sequencing with universal 16S rDNA primers D88 and E94 revealed a 100% identity with B. recurrentis A1. LBRF is a rare but emerging infectious disease among vulnerable displaced immigrants from the Horn of Africa. Since immigrants from endemic areas can carry the vector with them, the infection should be suspected even in subjects with compatible clinical features living in the same place where new arrival immigrants are hosted. Healthcare providers should be aware of this condition to implement adequate diagnostic, therapeutic, and public health measures.